2004
DOI: 10.1007/s11908-004-0025-2
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic infectious diseases in international travelers

Abstract: Skin lesions provide an important clue to the diagnoses of many infections in returned travelers. New information related to epidemiology, recognition, diagnosis, or management is described for the systemic infections--dengue fever, several of the rickettsial infections, African trypanosomiasis, and coccidioidomycosis. Many pathogens cause focal skin findings. Recent findings are presented for cutaneous leishmaniasis, Buruli ulcer, gnatho-stomiasis, cutaneous larva migrans, myiasis, tungiasis, and scabies. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 56 publications
2
6
0
1
Order By: Relevance
“…In our study, CLMs was the most frequently diagnosed helminthic skin disease (8%) as shown in other studies (Caumes et al. 1995; Wilson & Chen 2004; Freedman et al. 2006; Lederman et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, CLMs was the most frequently diagnosed helminthic skin disease (8%) as shown in other studies (Caumes et al. 1995; Wilson & Chen 2004; Freedman et al. 2006; Lederman et al.…”
Section: Discussionsupporting
confidence: 89%
“…Rickettsial infections cover the majority of skin diseases acquired in Southern Africa (Wilson & Chen 2004; Lederman et al. 2008; O’Brien 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the differential diagnoses of mucocutaneous lesions in the returned traveler, immigrant, or adoptee should be based on the morphology of the lesions, but the patient's symptoms, general medical, and exposure history must all be considered. [11][12][13][14][15][16][17] The physical examination and laboratory results must be integrated with the patient's vaccination and medication record. The travel destination(s), travel duration, living, work/recreation conditions, food and drink ingestion, and activities while traveling must all be taken into consideration.…”
Section: Migratory Skin Lesionsmentioning
confidence: 99%
“…[10][11][12] While human travel and migration are thought to cause the increasing incidence of tropical parasitic diseases in Europe and North America, global warming or climate tropicalization is implicated as one of the factors in the increase of human dermatophytes and mold infection. [13,14] …”
Section: Effect On Infectious Diseases Effect On Infectious Diseasesmentioning
confidence: 99%